2015
DOI: 10.1371/journal.pone.0117382
|View full text |Cite
|
Sign up to set email alerts
|

Sleep-Wake Evaluation from Whole-Night Non-Contact Audio Recordings of Breathing Sounds

Abstract: Study ObjectivesTo develop and validate a novel non-contact system for whole-night sleep evaluation using breathing sounds analysis (BSA).DesignWhole-night breathing sounds (using ambient microphone) and polysomnography (PSG) were simultaneously collected at a sleep laboratory (mean recording time 7.1 hours). A set of acoustic features quantifying breathing pattern were developed to distinguish between sleep and wake epochs (30 sec segments). Epochs (n = 59,108 design study and n = 68,560 validation study) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 52 publications
0
35
0
Order By: Relevance
“…This finding confirms early reports showing that snoring occurs mainly during inspiration, and that expiratory sound events are not common. 9,10,21,25 During sleep, upper airway resistance increases, 1-7 leading to amplification of air-pressure oscillations that are perceived as typical breathing sounds. 10,25 These sounds can vary from quiet (< 40 dB) to very loud snoring in the same subject.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This finding confirms early reports showing that snoring occurs mainly during inspiration, and that expiratory sound events are not common. 9,10,21,25 During sleep, upper airway resistance increases, 1-7 leading to amplification of air-pressure oscillations that are perceived as typical breathing sounds. 10,25 These sounds can vary from quiet (< 40 dB) to very loud snoring in the same subject.…”
Section: Discussionmentioning
confidence: 99%
“…9,10,21,25 During sleep, upper airway resistance increases, 1-7 leading to amplification of air-pressure oscillations that are perceived as typical breathing sounds. 10,25 These sounds can vary from quiet (< 40 dB) to very loud snoring in the same subject. 10 We found that, on average, 45% of the respiratory events during sleep generated air pressure oscillations that could be detected and analyzed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The commercialized product ResMed S+ classifies sleep stages using multiple sensors and a complex algorithm that is not openly available. By combining the ideas of Tauhidur Rahman et al [ 11 ], Eliran Dfana et al [ 15 ] and ResMed [ 16 ], we suggest that the fusion of noncontact microphone sensor and radar sensor data-based advanced signal processing algorithms would likely enhance the accuracy of sleep stage classification. Moreover, most previously-proposed sleep stage classification methods are aimed at average users, not patients with sleep disorders who actually require sleep stage information.…”
Section: Introductionmentioning
confidence: 99%